Trends in purchases and intake of foods and beverages containing caloric and low‐calorie sweeteners over the last decade in the United States. Issue 4 (25th March 2013) - Piernas, C.; Ng, S. W.; Popkin, B.
Summary: What is already known about this subject: Caloric sweetener (CS) intake in beverages and food has been linked with weight gain. Over the last 30 years, there have been important changes in consumption of caloric‐ and low‐calorie sweetened foods and beverages among children and adults in the United States. However, current food databases might not capture rapidly occurring changes in the U.S. food supply, such as the increased use of CS combined with low‐calorie sweeteners (LCS) in newly introduced or reformulated food products. What this study adds: We analyzed the Homescan commercial dataset (foods as purchased) and National Health And Nutrition Examination Survey (NHANES) of dietary intake (foods as consumed) to explore recent time trends in foods and beverages containing LCS, CS or both sweeteners in the United States. In terms of purchases (Homescan 2000–2010), although CS food and beverages continue declining, they remained high. We showed an important but previously unexplored trend in purchases of products that contain both LCS and CS, especially among households with children. In terms of intake (NHANES 2003–2010), children (2–18 years old) increased their consumption of LCS beverages and decreased intake of CS beverages. We found heterogeneity of consumption of CS and LCS foods and beverages across key socioeconomic status (SES) sub‐populations in both datasets. Background: Current food databases might not capture rapidly occurring changes in the food supply, such as the increased use of caloric (CS) and low‐calorie sweeteners (LCS) in products. Objective: We explored trends in purchases and intake of foods and beverages containing LCS, CS or both sweeteners over the last decade in the United States, as well as household and socioeconomic status (SES) predictors of these trends. Methods: We analyzed household purchases from Homescan 2000–2010 ( n = 140 352 households; 408 458 individuals) and dietary intake from National Health And Nutrition Examination Survey (NHANES) 2003–2010 ( n = 34 391 individuals). We estimated per capita purchases and intake (g or mL d −1 ) and percent of consumers of foods and beverages containing LCS, CS or both LCS + CS. We estimated change in purchases associated with SES and household composition using random‐effects longitudinal models. Results: From 2000 to 2010, percent of households purchasing CS products decreased, whereas that for LCS and LCS + CS products increased among all types of households and particularly among those with children. African–American, Hispanic and households with children had a higher % CS beverage purchases (+9, +4 and +3%, respectively, P < 0.001) and lower % LCS beverage purchases (−12, −5 and −2%, respectively, P < 0.001). Conclusions: During a period of declining purchases and consumption of CS products, we have documented an increasing trend in products that contain LCS and a previously unexplored trend in products with both LCS and CS, especially important among households with children.